Phosphate removal from synthetic and real wastewater using thermally treated seagrass residues of Posidonia oceanica - Photiou, Panagiota; Koutsokeras, Loukas E.; Constantinides, Georgios; Koutinas, Michalis; Vyrides, Ioannis (My University, 2021)
The objective of this work is to provide an insight into new low-cost adsorbent materials, for optimum recovery of phosphate from real wastewater. Several biowastes were tested for their capacity to adsorb phosphate: (a) orange peels, (b) coffee residues, (c) fish scales, (d) seagrass residues of P. oceanica, (e) biochar produced from olive kernels, and (f) biochar generated from vineyard prunings. Thermally treated seagrass residues exhibited the highest phosphate adsorption capacity among the aforementioned biowastes at 100 mg L−1 initial phosphate concentration. The optimum pre-treatment temperature and exposure time were determined as 500 °C and 1 h respectively, while washing with water the seagrass prior adsorption did not affect the adsorption process. Scanning electron microscopy and energy-dispersive X-ray spectroscopy showed that phosphate is more or less distributed within the majority of the thermally treated seagrass which relates to its high surface area owing to its tubular microstructure and thermal activation. Adsorption kinetics were best fitted to the pseudo-first order followed by the Freundlich isotherm indicating physical adsorption as the main mechanism. Phosphate removal from the supernatant of anaerobic digester and the liquid extracted from anaerobic dewatered sludge using thermally treated seagrass residues in neutral pH reached 81 and 86%, respectively. Under these conditions, thermally treated seagrass residues demonstrated high selectivity towards phosphate compared to NH4+ and organic compounds. To the best of our knowledge, this is the first study that demonstrates the use of thermally treated seagrass residues as a low-cost adsorbent material with high selectivity towards phosphate from real wastewater and reveals a new potential for using seagrass residues in a circular economy concept.
Keywords: Adsorption; Biowaste; Phosphate recovery; Posidonia oceanica; Seagrass residues; Anaerobic effluent